Criteria Review of Multifunctional Sidewalks in the Synergy Between Street Vendors and Pedestrian Paths (Case Study: Simpang Lima Area, Semarang) - Novian Rizqi Pramudita; Agung Budi Sardjono (Green Publisher Indonesia, 2025)
Sidewalks in Indonesia are often used for various purposes, one of which is by street vendors (PKL). Street vendors are often viewed negatively because they are considered to reduce pedestrian comfort. However, in some situations, street vendors can synergize with sidewalks and increase the vitality of public spaces. The purpose of this study is to evaluate the standards needed for multifunctional sidewalks that can serve as a forum for synergy between pedestrian paths and street vendor activities. The research employs a qualitative approach through a comprehensive literature review and systematic field observations, incorporating thematic analysis to evaluate sidewalk conditions against established urban design criteria. This study identifies eight critical factors affecting multifunctional sidewalks: effective width, street vendor layout, accessibility, pedestrian comfort, supporting activities, cleanliness, lighting, and legalization with management structures. The results show that the sidewalks in Simpang Lima can be categorized as multifunctional sidewalks. The layout of street vendors, supporting activities, lighting, and legalization are aspects that are already appropriate, while the aspects that are less optimal are effective width, accessibility, comfort, cleanliness, and facilities. Based on this study, it was found that the existence of street vendors can contribute to the vitality of public spaces in the Simpang Lima area, especially if it is well organized and the street vendor community participates in protecting the environment. It is hoped that this research can provide input for the city government in managing street vendors and enrich the study of urban design related to multifunctional sidewalks.